Air Force Chaplains' Perceived Effectiveness on Service Member's Resilience and Satisfaction. Issue 2 (3rd April 2017) - Cafferky, Bryan; Norton, Aaron; Travis, Wendy J.
Abstract : This study examined how 3, 777 active duty male United States Air Force service members' (SMs) rank and residence location moderated the associations between perceived chaplain effectiveness, SMs' resilience, family coping, marital satisfaction, and satisfaction with the Air Force (AF). A multiple-sample structural equation model was conducted with four subgroups of SMs who had received chaplain support: enlisted members living on base, enlisted members living off base, officers living on base, and officers living off base. Chaplain effectiveness was significantly related, both directly and indirectly, to SM's spirituality, resilience, family coping, marital satisfaction, and AF satisfaction. Resilience was significantly associated with increased AF satisfaction for all SMs, except for those living on base. However, living on base was found to strengthen the protective factor between family coping and relationship satisfaction. Rank was found to moderate the link between resilience and family coping. Family coping was significantly related to increased relationship satisfaction.